1983
DOI: 10.1128/mcb.3.8.1537
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of transcription during the cell cycle in toluenized Chlamydomonas reinhardi cells.

Abstract: A toluene-permeabilized cell system was established to examine the transcription of certain RNAs regulated during the cell cycle in Chlamydomonas reinhardi.The incorporation of [a-32P]UTP into RNA which hybridizes to specific cloned cDNA, such as P-tubulin, indicates that the cell cycle pattern of RNA accumulation may be controlled, in part, by differential transcription.The cell cycle in light-dark-synchronized cultures of Chlamydomonas reinhardi is marked by the periodic synthesis of certain cell cycle-regul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
1

Year Published

1984
1984
2005
2005

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 9 publications
0
2
1
Order By: Relevance
“…Previous studies of the cell cycle expression of LHCII, tubulin, and other nuclear-encoded genes of Chlamydomonas have demonstrated control of mRNA levels (1). Accumulation of these mRNAs may be determined by transcriptional and/or posttranscriptional controls in the nucleus or posttranscriptional control over mRNA stability in the cytoplasm (3,13). In contrast, the present analysis of three major chloroplast-encoded genes (rbcL, psbA, and psbD) shows that these mRNAs are abundant throughout the cell cycle.…”
Section: Discussioncontrasting
confidence: 61%
“…Previous studies of the cell cycle expression of LHCII, tubulin, and other nuclear-encoded genes of Chlamydomonas have demonstrated control of mRNA levels (1). Accumulation of these mRNAs may be determined by transcriptional and/or posttranscriptional controls in the nucleus or posttranscriptional control over mRNA stability in the cytoplasm (3,13). In contrast, the present analysis of three major chloroplast-encoded genes (rbcL, psbA, and psbD) shows that these mRNAs are abundant throughout the cell cycle.…”
Section: Discussioncontrasting
confidence: 61%
“…That is, if rRNA synthesis is actually somewhat depressed after deflagellation (12), then the 2.9-fold average increase in tubulin RNA synthesis we have measured would be an overestimate. DaUman et al (7) have made a related observation in Chlamydomonas. They reported that an approximate 2-fold increase in transcription of beta tubulin sequences preceding mitosis in permeabilized Chlamydomonas cells is insufficient to account for the 8-10fold increase in abundance which occurs at this time.…”
Section: Discussionmentioning
confidence: 89%
“…Our data are the first clear example of cell cycle regulation of tubulin mRNA transcription. Earlier reports of periodicity in Chlamydomonas (2,10,36) appear to be synchronization artifacts, since the periodicity disappears when cultures are returned to normal growth conditions (31). There is precedent in Chlamydornonas for the direct induction of tubulin gene transcription during flagellar regeneration.…”
Section: Tubulin Periodicitiesmentioning
confidence: 93%